A Ph Study for the Degradation of Acetaminophen with Iron Oxide Nanostructures - Bianca Lucas-Granados; Rita Sanchez-Tovar; Ramon Fernández-Domene; Jose Garcia-Anton (Chemical Engineering Transactions, 2019)
Nowadays, there is an increasing interest in the degradation of organic compounds in wastewater, since they are detrimental for the water quality. Different metal oxides have been studied as photocatalysts in the photoelectrocatalytic degradation of pharmaceutical products using UV light. Iron oxide nanostructures are a promising option in this field since their band gap (~ 2.1 eV, corresponding to ~590 nm) can absorb visible light, which in turn allows the degradation by using sunlight. Iron oxide nanostructures are known to be stable in alkaline solutions, but some organic compounds can vary their structure with pH. Then, a pH study is needed in order to stablish the optimum value to guarantee both the nanostructures and the organic molecule stability. In this work, acetaminophen (more known as paracetamol) is studied in different pH media (from pH 9 to pH 13) in order to evaluate the viability of iron oxide nanostructures as photocatalysts in the acetaminophen degradation process. Results showed that pH is a determinant parameter in the degradation process since the paracetamol UV-Vis spectrum varied with it. However, a pH compromise value is stablished in order to ensure the viability of the usage of iron oxide nanostructures in the acetaminophen degradation process.